Telemedicine in India: Transforming Patient Access and Satisfaction through Digital Healthcare Solutions - E, Rahul; Nupur Sinha; Ankitha Gururaj Bhatt (Gayaku Publisher, 2024)
Telemedicine in India: A revolutionary model of healthcare delivery has emerged to break geographical and accessibility barriers by dint of digital innovations. Telemedicine uses telecommunications technologies that permit remote consultations, diagnostics, and treatments, bridging healthcare disparities between urban and rural populations. Some of the key initiatives undertaken under government bodies like ISRO and the Ministry of Health & Family Welfare for e-Sanjeevani reflect its vast potential in creating greater access to healthcare. The COVID-19 pandemic has fueled the adoption of telemedicine, underlining its potential in delivering not only cost-effective but also time-effective health care. Despite the impressive growth that telemedicine still faces many challenges related to large-scale implementation, especially in improving infrastructure, regulatory frameworks, and professional training. Telemedicine's success in India is a good sign and a direction towards sustainability, equity, and an equal healthcare system for diverse populations and underserved pockets.